N-Acetylaspartylglutamate (NAAG) Pretreatment Reduces Hypoxic-Ischemic Brain Damage and Oxidative Stress in Neonatal Rats - Ewelina Bratek; Apolonia Ziembowicz; Elzbieta Salinska (MDPI AG, 2020)
N-acetylaspartylglutamate (NAAG), the most abundant peptide transmitter in the mammalian nervous system, activates mGluR3 at presynaptic sites, inhibiting the release of glutamate, and acts on mGluR3 on astrocytes, stimulating the release of neuroprotective growth factors (TGF-β). NAAG can also affect N-methyl-d-aspartate (NMDA) receptors in both synaptic and extrasynaptic regions. NAAG reduces neurodegeneration in a neonatal rat model of hypoxia-ischemia (HI), although the exact mechanism is not fully recognized. In the present study, the effect of NAAG application 24 or 1 h before experimental birth asphyxia on oxidative stress markers and the potential mechanisms of neuroprotection on 7-day old rats was investigated. The intraperitoneal application of NAAG at either time point before HI significantly reduced the weight deficit of the ischemic brain hemisphere, radical oxygen species (ROS) content and activity of antioxidant enzymes, and increased the concentration of reduced glutathione (GSH). No additional increase in the TGF-β concentration was observed after NAAG application. The fast metabolism of NAAG and the decrease in TGF-β concentration that resulted from NAAG pretreatment, performed up to 24 h before HI, excluded the involvement mGluR3 in neuroprotection. The observed effect may be explained by the activation of NMDA receptors induced by NAAG pretreatment 24 h before HI. Inhibition of the NAAG effect by memantine supports this conclusion. NAAG preconditioning 1 h before HI results in a mixture of mGluR3 and NMDA receptor activation. Preconditioning with NAAG induces the antioxidative defense system triggered by mild excitotoxicity in neurons. Moreover, this response to NAAG pretreatment is consistent with the commonly accepted mechanism of preconditioning. However, this theory requires further investigation.